Ensuring Quality Assurance in Technical and Vocational Education and Training (Journal of Technical and Vocational Education and Training, 2021)
Recent digital revolution is rapidly transforming the world of work and the skills profiles of many occupations. Major forces driving changes in the world of work include globalization, rapid advances in information and communications technology, changes in financial markets, new business strategies, new management practices and new forms of work. The uncertainty emerging from the fast changing environment, technological development has increased ethical and social responsibility. TVET was often a second choice of the students and was disregarded as a significant player in academic orientation in some years back. Now, that statement has been slowly discarded since awareness increased and through quality in education it is proved that TVET are the best providers of knowledgeable and skilled workers in the 21st century. Quality assurance in TVET is a concept that is concerned with high performance in entire academic process involving activities such as teaching, learning, infrastructure, students’ behavior and so on. The TEVT sector and its policy makers respond rapidly to the changing scenario. Good quality education is very necessary in the total development of the student, which ensures proper development, job prospects and the realization of academic goals and objectives. There are varied factors working against the realization of quality TVET. Practical partnerships between public and private actors will have an increasingly important role to play in the delivery of TVET programs so that the fresh TVET graduates have to be world class and the education quality has to maintain of global standards. This paper outlines and discusses the relevancy and quality assurance need in TEVT to meet the requirements in the coming future.